A review paper on student-graduate advisory expert system - Tawafak, Ragad Moufaq; Al-Farsi, Ghaliya Musalam Salim; Awanis, Romli; Jabbar, Jasiya; Malik, Sohail Iqbal; AlSideiri, Abir (Institute of Electrical and Electronics Engineers Inc., 2020)
Academic advising of the postgraduate students is considered as a fundamental rule and one of the significant positive services and responsibilities for the academic staff follow up in most of the e-leading educations. The expert system is considered as one of most achievement areas in artificial intelligence and highly appreciated for application with e-learning and teaching methods. The aim of this paper, is to survey the most expert systems used in advisory model and replaced with the manual registration and advising system of face to face communication and discussion in Instructor office. The method used of determined the key factors related to student advising and expert system models though open access databases. The finding of this section reviews out nine selected expert systems in order to explore the strengths, and limitations of existing expert system approaches to advising undergraduate students.